2023
DOI: 10.1371/journal.pgen.1011063
|View full text |Cite
|
Sign up to set email alerts
|

Autophagic dysfunction and gut microbiota dysbiosis cause chronic immune activation in a Drosophila model of Gaucher disease

Magda L. Atilano,
Alexander Hull,
Catalina-Andreea Romila
et al.

Abstract: Mutations in the GBA1 gene cause the lysosomal storage disorder Gaucher disease (GD) and are the greatest known genetic risk factors for Parkinson’s disease (PD). Communication between the gut and brain and immune dysregulation are increasingly being implicated in neurodegenerative disorders such as PD. Here, we show that flies lacking the Gba1b gene, the main fly orthologue of GBA1, display widespread NF-kB signalling activation, including gut inflammation, and brain glial activation. We also demonstrate inte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 85 publications
2
9
0
Order By: Relevance
“…In keeping with the autophagy impairments in GD, increased LC3-II/LC3-I ratios and p62 accumulation, both consistent with a defect in autophagosome-lysosome fusion, have been observed in mouse [52], patient iPSCderived neuronal models [50] and fly models of nGD [48,49]. Moreover, studies in iPSC-derived midbrain dopaminergic neurons from patients with GBA1 mutations demonstrated an increase in both LC3 and LAMP1, with a low co-localization index, suggesting a block specifically at the fusion stage of autophagy [53].…”
Section: Parkinson's Disease Genes Map To Endolysosomal Trafficking P...supporting
confidence: 67%
See 3 more Smart Citations
“…In keeping with the autophagy impairments in GD, increased LC3-II/LC3-I ratios and p62 accumulation, both consistent with a defect in autophagosome-lysosome fusion, have been observed in mouse [52], patient iPSCderived neuronal models [50] and fly models of nGD [48,49]. Moreover, studies in iPSC-derived midbrain dopaminergic neurons from patients with GBA1 mutations demonstrated an increase in both LC3 and LAMP1, with a low co-localization index, suggesting a block specifically at the fusion stage of autophagy [53].…”
Section: Parkinson's Disease Genes Map To Endolysosomal Trafficking P...supporting
confidence: 67%
“…Given the role of the lysosome in several intracellular degradative processes, including the various forms of autophagy, defects in such pathways are increasingly being linked to GD [46][47][48]. Lysosomal-autophagic dysfunction has been well described in GD and PD linked to GBA1 mutations (GBA-PD) [46][47][48][49]. Studies in post-mortem GBA-PD brains demonstrated that mutant forms of GCase at the lysosomal surface impair CMA degradation of αSyn [37].…”
Section: Parkinson's Disease Genes Map To Endolysosomal Trafficking P...mentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, Smpd1 displays a secreted rather than a lysosomal role in Drosophila embryos. Evidence of an increase in autophagosomes is in keeping with other Drosophila lysosomal storage disorder (LSD) models, underscoring common mechanisms between diverse LSDs (Atilano et al, 2023, Hull et al, 2024). Furthermore, Smpd1 is abundantly expressed in adulthood in the glia and fat body, suggesting important roles in adulthood, and adult-specific knockout of Smpd1 may produce more canonical LSD phenotypes.…”
Section: Discussionsupporting
confidence: 56%